Analisis Faktor Penyebab Keterlambatan Penyelesaian Studi Mahasiswa Prodi Ilmu Alquran dan Tafsir UINSU - Fani Aqila; Fani Sefriani; Ramasda Febrianto; Dwi Wulandari; M. Rizky Ramadhan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Students are an important community in a university. The ultimate goal of a student in a college is to complete a final assignment. However, many students experience problems with delays in completing their final assignments. The aim of this research is to analyze what factors hinder and delay students in completing their final assignments. This type of research uses qualitative research where interviewing sources from the Koran science and tafsir study program. The results of this research are that the inhibiting factors in student graduation include lecturer behavior that makes things difficult for students, a lack of synchronization of information between the study program and the faculty, the presence of students who work part-time, and a lack of time and motivation for a student.